Immigration Policy in the European Union: Opportunities, Challenges and Dilemmas - Anna Yulia Hartati (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
This  article  describes  the  immigration  policy  dilemma  in  the  European  Union.  Immigration  Issues strengthened  along  with  the  wave  of  migrants  to  Europe.  This  raises  a  problem  that  is  quite  complex.  The phenomenon of immigration is causing changes in the European countries. One important factor that has changed is the policy. On the one hand, the provision of legal migration program of the government in the recipient country is very limited because European countries now also perform a special selection to filter the migrants who have high skills.  The  existence  of  this  screening  program  indicative  of  the  problems  of  the  workers  and  the  short-term discrepancies between supply and demand in many European countries. The existence of various problems related to immigrants eventually led to a dilemma in policy making on immigration in the European Unio n. This dilemma can be divided into four categories, including a dilemma: labor migration policy, migration control policies, protection and asylum systems, as well as integration policy. The author uses the research methods used to use the analysis of qualitative  research,  which  the  authors  create  a  description,  picture  or  painting  in  a  systematic,  factual,  accurate information on the facts, nature and the relationship between the phenomenon investigated.Keywords: immigration policy, labor migration, protection and asylum systems, policy dilemma